2017
DOI: 10.3892/ol.2017.7280
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of S‑allyl‑L‑cysteine via induction of apoptosis in human bladder cancer cells

Abstract: Abstract.To exa m i ne the anticancer effects of S-allyl-L-cysteine (SAC) in human bladder cancer cells and to identify possible molecular mechanisms, bladder cancer cell lines (HTB5, HTB9, JON, UMUC14, T24, and cisplatin resistant-T24R2) were incubated with SAC, and cell proliferaproliferation was measured using the Cell Counting Kit-8 assay and clonogenic assay. Cell cycle and apoptosis were evaluated by flow cytometry. Expression levels of apoptosis-and cell cycle-associated proteins were analyzed by wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…The results were supported by those of the study by Ho et al. (2018), which showed that SAC promoted S‐phase inactivation and apoptosis of A2780 ovarian cancer cells, which is associated with the downregulation of Bcl‐2 and the upregulation of Bax and caspase‐3. SAC induced apoptosis in T24 and T24R2 bladder cancer cells, inhibiting the proliferation of these cells, altering the expression of apoptosis and cell cycle markers, and disrupting the cell cycle.…”
Section: Bioactivities Of S‐allyl Cysteine (Sac)supporting
confidence: 83%
See 1 more Smart Citation
“…The results were supported by those of the study by Ho et al. (2018), which showed that SAC promoted S‐phase inactivation and apoptosis of A2780 ovarian cancer cells, which is associated with the downregulation of Bcl‐2 and the upregulation of Bax and caspase‐3. SAC induced apoptosis in T24 and T24R2 bladder cancer cells, inhibiting the proliferation of these cells, altering the expression of apoptosis and cell cycle markers, and disrupting the cell cycle.…”
Section: Bioactivities Of S‐allyl Cysteine (Sac)supporting
confidence: 83%
“…Garlic can also help reduce blood pressure. One of the most intriguing properties of garlic is its anticancer activity; notably, it is used to prevent stomach and colon cancers (Ho et al., 2018). Platelet aggregation and hyperlipidemia have also been shown to be reduced by garlic (Rahman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the most widely used processing method for removing the unpleasant odor and taste of garlic is heat treatment (García-Villalón et al, 2016). During heat treatment, various physicochemical changes occur, including changes in odor, nutrient content, flavor and color.An important compound, S-Allylcysteine, is produced in large amounts during the aging process of garlic and is a key compound responsible for the multiple pharmacological activities of garlic such as antioxidant, anticancer, and neurotrophic activities (Baluchnejadmojarad, Kiasalari, Afshin-Majd, Ghasemi, & Roghani, 2017;Ho et al, 2018). S-Allylcysteine is formed by the enzymatic hydrolysis of γ-glutamyl-S-allyl cysteine (GSAC) by γ-glutamyl transpeptidase (γ-GTP) (Kodera et al, 2002).…”
mentioning
confidence: 99%
“…Among the natural compound, garlic, a species of the Allium genus, has been used throughout recorded history for both culinary and medicinal purposes (20,21,24). In our previous study, as well as in numerous other reports, it was observed that AGE induced a decrease in the viability of several human cancer cell lines (1,20,24,41). This result represents an interesting finding, since in conventional cancer chemotherapy, numerous issues hamper successful treatment.…”
Section: Discussionmentioning
confidence: 58%